Strategi Guru Sekolah Dasar Dalam Menumbuhkan Kreativitas Siswa Melalui Pembelajaran Berbasis Proyek - Rahmatika; Haifaturrahmah; Nursina Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Contextual project planning with themes close to students' daily lives; (2) the application of collaborative methods through group discussions and assignments according to ability; (3) gradual guidance by providing initial direction as well as space for exploration; and (4) product and process-based evaluation that emphasizes originality, innovation, and the development of student ideas. This strategy has been proven to be able to generate creative ideas, increase the courage This study aims to analyze the strategies of elementary school teachers in fostering student creativity through the implementation of Project Based Learning (PjBL). Creativity is an essential 21st-century skill that needs to be developed from the elementary education level, but learning practices in elementary schools still tend to be oriented towards memorization and cognitive achievement. This study uses a descriptive qualitative approach with three teachers and fifteen students selected through purposive sampling in one elementary school. Data were collected through in-depth interviews, classroom observations, and documentation studies, then analyzed using thematic analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers apply four main strategies, namely: (1to express opinions, and foster students' self-confidence in their work. These findings confirm the importance of the teacher's role as a facilitator of creative learning and strengthen the results of previous research on the effectiveness of PjBL, by adding a new contribution in the form of details of teachers' pedagogical strategies in the elementary school context.Kata Kunci: creativity, teacher strategies, elementary schools, project-based learning